Standardized endocystectomy technique for surgical treatment of uncomplicated hepatic cystic echinococcosis - Saeedi, Mohammed al; Khajeh, Elias; Hoffmann, Katrin; Ghamarnejad, Omid; Stojković, Marija; Weber, Tim; Golriz, Mohammad; Strobel, Oliver; Junghanss, Thomas; Büchler, Markus W.; Mehrabi, Arianeb (PLoS neglected tropical diseases, 2019)
Background: Two surgical options are available for cystic echinococcosis (CE). The two principal approaches are radical (resection of the cyst) and conservative (evacuation of the cyst content and partial removal of the cyst capsule). Here, we describe a standardized endocystectomy technique for hepatic echinococcosis. Subjects and methods Twenty-one patients (male/female: 4/3; median age: 28 years) with uncomplicated, isolated hepatic CE (cyst stages WHO CE1, 2, 3a, and 3b) that were treated with the standardized endocystectomy described in this paper. Before the operation and during the follow-up period (mean: 33.8 months, median: 24 months), patients underwent clinical and sonographical and/or magnetic resonance imaging assessment during regular visits managed by an interdisciplinary team. Results: Forty-seven cysts were treated with the standardized endocystectomy technique. The median number of cysts per patient was two (range: 1-8). Nine patients (43%) had a single cystic lesion. The median operation time was 165 minutes and the median intraoperative bleeding volume was 200 mL. The median hospital stay was nine days (range: 6-28 days). Morbidity (Clavien-Dindo III) occurred in four patients (19%). No mortality and no recurrence were found during the median follow-up time of 24 months. Conclusions: The standardized endocystectomy technique presented is a safe procedure with acceptable morbidity, no mortality, and without recurrences in our patient series. Important components of our CE management are interdisciplinary patient care, adequate diagnostic work-ups, and regular pre- and postoperative visits, including long-term follow-up for early and reliable capture of recurrences. Author summary: Cystic echinococcosis (CE) is a parasitic disease caused by ingestion of the larval stage of Echinococcus granulosus. The liver is the most commonly infected organ. There are currently four treatments for CE: surgery, percutaneous treatment, medical treatment (benzimidazoles), and watch-and-wait strategy. Treatment is decided based on the WHO cyst staging. The surgical techniques employed depend on the cyst location and related complications (e.g. cyst-biliary fistulas, rupture, and secondary bacterial infection). The two principal surgical approaches are radical (resection of the cyst) and conservative (evacuation of the cyst content and partial removal of the cyst capsule) surgeries. In this study, we presented a conservative surgical approach, a standardized endocystectomy technique, that is suitable for surgical residents. This standardized endocystectomy technique is a safe procedure with acceptable morbidity, no mortality, and without recurrences in our patient series. Important components of CE management are interdisciplinary patient care, adequate diagnostic work-ups, and regular pre- and postoperative visits, including long-term follow-up for early and reliable capture of recurrences.
Gesehen am 12.09.2019